RESPON PERTUMBUHAN TANAMAN KACANG HIJAU VARIETAS WALET TERHADAP PEMBERIAN INOKULAN RfflZOBIUM DAN MIKORIZA DI LAHAN MASAM - Subadri Abdulkadir (BERITA BIOLOGI, 1999)
The study on the growth response of mungbean Walet variety inoculated by Rhizobium and VA-Mycormiza inoculant carried out done at UPT-BBOK-UPI, Bergen, Lampung, using Competely Randomized Block Design. Five treatments by using Rhizobium, 5 treatments by using mixed Rhizobium and Myco.rrhiza, 1 treatment by using Mycorrhiza. The plant, without inoculated and without fertilized, the plants without inoculated but fertilized by using urea, the plants without inoculated but fertilized by using TSP, and the plants without inoculated but fertilized by using urea and TSP as control. Each treatment has 3 replications. The height and the weight of the plants, the weight of nodules had been weighted after 30 days planting. The result of the research showed that the plants by giving inoculant better growth compare to the plants without inoculated and fertilized. The weight of plants and root is compered which the plants by giving Rhizobium and Mycorrhiza to the plants without inoculated and fertilized was not significant. However, in the height and the wight of nodules of some treatments were significant to the control.